The calpain system is associated with survival of breast cancer patients with large but operable inflammatory and non-inflammatory tumours treated with neoadjuvant chemotherapy - Storr, Sarah J.; Zhang, Siwei; Perren, Tim; Lansdown, Mark; Fatayer, Hiba; Sharma, Nisha; Gahlaut, Renu; Shaaban, Abeer; Martin, Stewart G. (Impact Journals, 2016)
The calpains are a family of intracellular cysteine proteases that function in a variety of important cellular functions, including cell signalling, motility, apoptosis and survival. In early invasive breast cancer expression of calpain-1, calpain-2 and their inhibitor, calpastatin, have been associated with clinical outcome and clinicopathological factors. The expression of calpain-1, calpain-2 and calpastatin was determined using immunohistochemistry on core biopsy samples, in a cohort of large but operable inflammatory and non-inflammatory primary breast cancer patients treated with neoadjuvant chemotherapy. Information on treatment and prognostic variables together with long-term clinical follow-up was available for these patients. Diagnostic pre-chemotherapy core biopsy samples and surgically excised specimens were available for analysis. Expression of calpastatin, calpain-1 or calpain-2 in the core biopsies was not associated with breast cancer specific survival in the total patient cohort; however, in patients with non-inflammatory breast cancer, high calpastatin expression was significantly associated with adverse breast cancer-specific survival (P=0.035), as was low calpain-2 expression (P=0.031). Low calpastatin expression was significantly associated with adverse breast cancer-specific survival of the inflammatory breast cancer patients (P=0.020), as was low calpain-1 expression (P=0.003). In conclusion, high calpain-2 and low calpastatin expression is associated with improved breast cancer-specific survival in non-inflammatory large but operable primary breast cancer treated with neoadjuvant chemotherapy. In inflammatory cases, high calpain-1 and high calpastatin expression is associated with improved breast cancer-specific survival. Determining the expression of these proteins may be of clinical relevance. Further validation, in multi-centre cohorts of breast cancer patients treated with neoadjuvant chemotherapy, is warranted.